Network pharmacology: an efficient but underutilized approach in oral, head and neck cancer therapy—a review - Muthuramalingam, Pandiyan; Jeyasri, Rajendran; Varadharajan, Venkatramanan; Priya, Arumugam; Dhanapal, Anand Raj; Shin, Hyunsuk; Thiruvengadam, Muthu; Ramesh, Manikandan; Krishnan, Murugesan; Omosimua, Rebecca Oziohu; Sathyaseelan, Divyan Devasir; Venkidasamy, Baskar (Frontiers in Pharmacology, 2024)
The application of network pharmacology (NP) has advanced our understanding of the complex molecular mechanisms underlying diseases, including neck, head, and oral cancers, as well as thyroid carcinoma. This review aimed to explore the therapeutic potential of natural network pharmacology using compounds and traditional Chinese medicines for combating these malignancies. NP serves as a pivotal tool that provides a comprehensive view of the interactions amongbetween compounds, genes, and diseases, thereby contributing to the advancement of disease treatment and management. In parallel, this review discusses the significance of publicly accessible databases in the identification of oral, head, and neck cancer-specific genes. These databases, including those for head and neck oral cancer, head and neck cancer, oral cancer, oral cancer, and genomic variants of oral cancer, offer valuable insights into the genes, miRNAs, drugs, and genetic variations associated with these cancers.They serve as indispensable resources for researchers, clinicians, and drug developers, contributing to the pursuit of precision medicine and improved treatment offor these challenging malignancies. In summary, advancements in NP could improve the globalization and modernization of traditional medicines and prognostic targets as well as aid in the development of innovative drugs. Furthermore, this review will be an eye-opener for researchers working on drug development from traditional medicines by applying NP approaches.